Analysis of Factors Affecting the Decision of the JABODETABEK Community in Using Equity Crowdfunding Platform - Emil Robert Kaburuan, Fauzan Nasafi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This research analyzes the factors that influence the decision to use the equity funding platform in Indonesia. Equity crowdfunding platform is a platform that organizes the crowdfunding process, where investors will receive an equity instrument that provides a share of ownership or a share of future income. This research model is compiled based on the merging of previous research models related to the intention to use the equity funding platform, such as Financing Objectives, Number of Shares Assigned, Number of Inquiries, Familiarity with the Company or Its Product, Target Attractiveness and Campaign Specification. Sources of data were collected from respondents using the equity crowdfunding platform who are JABODETABEK people through a questionnaire, and obtained 428 respondents. The data were analyzed using the SmartPLS 3, and the results show that the variable Familiarity with the Company or Its Product and Target Attractiveness affects people's decisions in using the equity crowdfunding platform.